Performance Evaluation of Liquid Mixing in a T-Junction Passive Micromixer with a Twisted Tape Insert - Kurnia, J.C. (American Chemical Society, 2020)
An innovative passive mixing enhancement method by using a T-junction micromixer with twisted tape is proposed and evaluated. A three-dimensional model is developed and validated by considering the single-phase mixing of the laminar Newtonian miscible fluid. Several key parameters are evaluated, namely, the inlet Reynolds number, twisted tape width, nature of the twisted tape (solid and porous), and permeability of the porous tape. Mixing index, pressure drop, and performance index, defined as the ratio of mixing enhancement over the ratio of friction factor, are compared. The results suggest that adding twisted tape can enhance the mixing index by almost twice at the cost of a higher pressure drop. Porous tape with the permeability of 10-10 m2 is found to have the best performance at low to medium Reynolds numbers, while solid twisted tape improves the performance at a higher Reynolds number. The proposed method can be used to enhance mass transfer for micromixers in chemical processes and pharmaceutical applications. Copyright Â© 2019 American Chemical Society.